The concept of subsumption in the early historical periods in the Andes - Silva de la Roca, Edwin Angel (2015)
With reference to Marx and the Marx’s reading done by Enrique Dussel, we develop the concept of real subsumption and formal subsumption for Andean early societies, from the category of living work and the object as use value and exchange; considering both social, and environmental. Additionally, we do an interpretative proposal of the way it conducts social relations of consumption to better understand the social relations of production. Also, realize the essence of the historical process in the Andes around early societies (circa 15.200 to 2.800 years BC), based on different modos de vida, which give way to an early social complexity. Finally, we propose some categories for these early periods, from the theoretical contributions of so-called Latin American Social Archaeology